Evaluation of Zoiiran physical properties according to ISO 3107, BS 7214 and EN 23107 - Shahabi S.; Tehrani Sefat M. (Tehran University of Medical Sciences, 2004)
Statement of Problem: With due attention to the control of quality of dental materials and its role in"nimprovement of quality and accuracy of treatment, in this research, Zoiiran made in Golchai company was"nevaluated according to international standards."nPurpose: The aim of this study was the evaluation of properties of Zinc-oxide-eugenoi reinforced cement"nwith trade name "Zoiiran"."nMaterials and Methods: According to ISO 3107, BS 7214, EN 23107 standards (1991), the number of"nsamples were as follows: 2 for setting time, 5 for compressive strength, 4 for disintegration and 3 for film"nthickness testing. The experiments were followed standards instructions."nResults: Setting time was between 5.57-6.03 min. The compressive strength was between"n21.29-25.79 MPa. Zoiiran had about 1.3-1.5 % disintegration. Finally, the film thickness was between"n11-11.5 u."nConclusion: According to mentioned experiments, physical properties of Zoiiran as temporary cement of"nfixed-prosthodontic (Typel-class I) and base liner (Type IV-class I), were similar to stated standards.